Kesiapsiagaan Civitas Akademika dalam menghadapi Bencana Gempa Bumi di Sekolah Menengah Kejuruan Nusantara Kota Palu - syahrir, sabri; Miftahul Haerati Sulaiman; Ummu Kamilah; Putra Pratama Ramadhan (Health Safety Environment, 2025)
Background: The earthquake incident on September 28th 2018 in Central Sulawesi resulted in 2,256 people dying and the loss figure from this disaster reached 13.82 trillion rupiah. So it is necessary to create a preparedness system to minimize deaths and losses due to earthquakes. This research investigates the preparedness of the school members in facing earthquake disasters at SMK Nusantara, Palu City. Method: The type of research used is quantitative with a descriptive observational method. The sampling technique applied is total sampling, resulting in a total of 37 samples. The collected data were then statistically analyzed using univariate analysis. Results: The research results illustrate the preparedness of the school members workers at SMK Nusantara Kota Palu based on several variables. In the variable of knowledge and attitude towards disasters, the majority of the school members falls into the good category, with a percentage of 83.8%. In the variables of responding to the early warning system and resource mobilization, they fall into the prepared category, each with a percentage of 51.4%. Meanwhile, in the variable of emergency response planning, they are categorized as unprepared, with a percentage of 62.2%. Conclusion: The majority of the school members at SMK Nusantara Kota Palu falls into the prepared category regarding knowledge and attitude, early warning systems, and resource mobilization. However, they are not yet prepared in emergency response planning, which is one of the indicators of preparedness. Keywords: School Members; Earthquake; Preparedness; School